1999
DOI: 10.1677/joe.0.1630099
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of activin A, inhibin A and follistatin in human amnion, choriodecidual and placental tissues at term and preterm

Abstract: To investigate labour-associated changes in production of activin and related hormones by gestational tissues we prepared extracts from amnion, choriodecidual and placental tissues delivered at term before labour (TNL; n=15), at term after spontaneous labour (TSL; n=15) or preterm (PTD; n=31) and measured concentrations of inhibin A, activin A and follistatin by ELISA. Activin concentrations in placental tissues were significantly (Mann-Whitney U-test; P<0·05) elevated with term labour (pg/mg protein, median; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Using human explant tissue culture, it has been reported that inhibins A and B are secreted by the chorion laeve, whereas only inhibin A is secreted by the placenta. Furthermore, only low concentrations of both dimeric inhibins are secreted by the decidua parietalis and amnion (Riley et al 1996, Keelan et al 1999 and the mRNA for the subunits of inhibin A has been detected in human placenta (Petraglia et al 1987). It has been concluded that the placenta is a major source of circulating inhibin A in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Using human explant tissue culture, it has been reported that inhibins A and B are secreted by the chorion laeve, whereas only inhibin A is secreted by the placenta. Furthermore, only low concentrations of both dimeric inhibins are secreted by the decidua parietalis and amnion (Riley et al 1996, Keelan et al 1999 and the mRNA for the subunits of inhibin A has been detected in human placenta (Petraglia et al 1987). It has been concluded that the placenta is a major source of circulating inhibin A in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three activins -A, B and AB -that have been identified in human tissues, activin A is the predominant form in pregnancy (Qu & Thomas 1995, Fowler et al 1998. The placenta and fetal membranes are the main sources of circulating activin A (Rabinovici et al 1992, Petraglia et al 1997, Keelan et al 1999. In early and mid pregnancy, maternal serum activin A levels are stable and low, rising dramatically from approximately 24 weeks of gestation, reaching peak levels proximate to term (Petraglia et al 1993a, Fowler et al 1998, Schneider-Kolsky et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Possible sources are fetal membranes and neutrophils with well-established roles on fighting infection (17,31). Our current data showed that intra-amniotic infection upregulated activin-A directly related to the level of AF inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…We investigated AF samples from 168 women pregnant with singletons who had a clinically indicated amniocentesis to rule-out infection. Samples were retrieved by transabdominal amniocentesis for the purpose of i) second trimester genetic karyotyping [Gestational Age (GA), median [IQR range]: 19 [18 -20] weeks, n ϭ 19); ii) third trimester fetal lung maturity testing (GA: 36 [36 -37] weeks, n ϭ 20); iii) rule-out AF infection in women who had preterm labor contractions refractory to tocolysis, PPROM or advanced cervical dilatation (Ͼ3 cm) (GA: 28 [25][26][27][28][29][30][31] weeks, n ϭ 129). Ruleout AF infection cases were further grouped by timing of birth (term or preterm), membrane status at amniocentesis (intact membranes or PPROM) and microbiologic culture results of the AF (positive or negative).…”
Section: Methodsmentioning
confidence: 99%